2021
DOI: 10.3389/fphys.2021.718667
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Epinephrine During Experimental Hypothermia (32°C) With Spontaneous Circulation in an Intact Porcine Model

Abstract: Aims: Rewarming from accidental hypothermia and therapeutic temperature management could be complicated by cardiac dysfunction. Although pharmacologic support is often applied when rewarming these patients, updated treatment recommendations are lacking. There is an underlying deficiency of clinical and experimental data to support such interventions and this prevents the development of clinical guidelines. Accordingly, we explored the clinical effects of epinephrine during hypothermic conditions.Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…β-receptor stimulation through administration of isoprenaline, has earlier been suggested to lack inotropic effects during hypothermia when administered to rats [ 37 , 38 ]. However, recent studies have shown that β1-stimulus by epinephrine has positive inotropic effects on pigs cooled down to 32 °C [ 6 ], which corresponds with the findings in the present study. A case report from 2015 also indicates that isoprenaline had beneficial effect in treatment of VF in an accidental hypothermia patient [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…β-receptor stimulation through administration of isoprenaline, has earlier been suggested to lack inotropic effects during hypothermia when administered to rats [ 37 , 38 ]. However, recent studies have shown that β1-stimulus by epinephrine has positive inotropic effects on pigs cooled down to 32 °C [ 6 ], which corresponds with the findings in the present study. A case report from 2015 also indicates that isoprenaline had beneficial effect in treatment of VF in an accidental hypothermia patient [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, treatment guidelines for accidental hypothermia recommend withholding any drug administration until a core temperature of at least 30 °C is reached [ 2 ]. However, recent studies have shown that phosphodiesterase 3 (PDE3)-inhibitors and β-receptor stimulators have the potential to alleviate HCD in vivo [ 6 8 ], and that the cellular mechanisms of these drugs remain intact at temperatures down to 20 °C [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Well-known β-receptor agonists, such as epinephrine and isoproterenol, increase cAMP levels through the adenylyl cyclase (AC) pathway. Studies in a rat model of severe hypothermia suggest that these drugs increase SVR without simultaneous positive inotropic effect ( Dietrichs, Sager and Tveita, 2016 ) but species-dependent differences exist ( Mohyuddin et al, 2021 ). More promisingly, in vivo studies performed in rat models, have demonstrated that PDE3 inhibitors, such as milrinone and levosimendan, have positive effects on stroke volume and cardiac output, almost restoring these parameters to baseline levels during rewarming ( Detrichstrichs et al, 2014a; Dettrichstrichs et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%